National Outcomes for Open Ventral Hernia Repair Techniques in Complex Abdominal Wall Reconstruction. Issue 8 (August 2015) - Ross, Samuel W.; Oommen, Bindhu; Huntington, Ciara; Walters, Amanda L.; Lincourt, Amy E.; Kercher, Kent W.; Augenstein, Vedra A.; Heniford, B. Todd
Modern adjuncts to complex, open ventral hernia repair often include component separation (CS) and/or panniculectomy (PAN). This study examines nationwide data to determine how these techniques impact postoperative complications. The National Surgical Quality Improvement Program database was queried from 2005 to 2013 for inpatient, elective open ventral hernia repairs (OVHR). Cases were grouped by the need for and type of concomitant advancement flaps: OVHR alone (OVHRA), OVHR with CS, OVHR with panniculectomy (PAN), or both CS and PAN (BOTH). Multivariate regression to control for confounding factors was conducted. There were 58, 845 OVHR: 51, 494 OVHRA, 5, 357 CS, 1, 617 PAN, and 377 BOTH. Wound complications (OVHRA 8.2%, CS 12.8%, PAN 14.4%, BOTH 17.5%), general complications (15.2%, 24.9%, 25.2%, 31.6%), and major complications (6.9%, 11.4%, 7.2%, 13.5%) were different between groups ( P < 0.0001). There was no difference in mortality. Multivariate regression showed CS had higher odds of wound [odds ratio (OR) 1.7, 95% confidence interval (CI) 1.5–2.0], general (OR 1.5, 95% CI: 1.3–1.8), and major complications (OR 2.1, 95%, CI: 1.8–2.4), and longer length of stay by 2.3 days. PAN had higher odds of wound (OR 1.5, 95%, CI: 1.3–1.8) and general complications (OR 1.7, 95% CI: 1.5–2.0). Both CS and PAN had higher odds of wound (OR 2.2, 95%, CI: 1.5–3.2), general (OR 2.5, 95%, CI: 1.8–3.4), and major complications (OR 2.2, 95%CI: 1.4–3.4), and two days longer length of stay. In conclusion, patients undergoing OVHR that require CS or PAN have a higher independent risk of complications, which increases when the procedures are combined.